Penatalaksanaan kasus bimaxillary dental protrusion disertai gigi anterior berjejal berat - Nofrizal, Riko (Fakultas Kedokteran Gigi Universitas Trisakti, 2024)
Background: Bimaxillary dental protrusion accompanied by crowding is a case of malocclusion which has high prevalence in the Asian region. Treatment of bimaxillary dental protrusion accompanied crowding case generally involves the extraction of four firat premolar to obtain the space required to correct crowding and retraction of the anterior teeth. Objective: This case report explain about the treatment of bimaxillary dental protrusion accompanied by severe crowding. Case: The patient has a convex soft tissue pofile, bimaxillary dental protrusion accompanied by severe crowding. Case treatment: Treatment begins with extracting the four first premolar to create space, so that the anterior crowding can be repositioned properly. The anterior retraction is performed to correct the convex facial profile. After 20 months of treatment, the patient’s occlusion and aesthetics improved. Conclusion: An appropriate treatment plan is very necessary for the treatment of bimaxillary dental protrusion accompanied by severe crowding to obtain maximum treatment results